Optimism Dimensions in Interstellar Movie by Christopher Nolan - Palupi, Muji Endah; Adrian, Fadilah; Susilawati, Susilawati (SCOPE: Journal of English Language Teaching, 2024)
The purpose of this research is to analyze the optimism dimensions and impacts of optimism found in the main characters in Interstellar, a movie by Christopher Nolan released in 2014. A descriptive qualitative method with a content analysis method was employed in this study. The data were collected using a literary study technique from the movie conversation. The data were analyzed using the optimism theory suggested by Seligman (2006). The results revealed that the optimistic dimensions found in this movie consist of permanence or immortality, pervasiveness, and personalization. These values are viewed as having impacts on the other movie characters, which reduces the attitude of pessimism and prejudice as well as leads experience to an optimistic stance. The findings imply that optimism values influence people to act, or even change their perspectives. A much deeper investigation of another crucial value in this movie is recommended as a reflection of the current literary works.